Culinary Practical Online Class: A Development of Study Method amid COVID-19 Pandemic - Grasielda, Ivana; Yuwono, Victor Kurniawan (Institut Pariwisata Trisakti, 2022)
This study aims to develop learning methods in online culinary practice classes using MOOC (Massive Open Online Class). This research is descriptive exploratory with qualitative methods to find out stakeholders' weaknesses, strengths, and expectations for an effective MOOC design in online culinary practice classes. Stakeholders consist of students, permanent lecturers, part-time lecturers, and experts spread across all regencies/cities in East Java and other regions in Indonesia. The study results concluded that the MOOC design was able to meet the expectations of stakeholders, namely that practicum classes could be delivered effectively even though the duration was less than the classes before the new normal era. An effective MOOC means that all components must be planned holistically for both lecturers and students, but lecturers are also obliged to complete the teaching components before learning begins. Starting with determining the theme as a focus, then designing teaching methods supported by giving assignments, assessments, and feedback. This component must have a conducive learning atmosphere, which requires full cooperation and trust between lecturers and students. The overall MOOC plan should be visualized and communicated regularly from the first week of learning. Keywords: Online, Blended Learning, Project-Based Learning, Practical, Culinary